2007
DOI: 10.1016/j.biopsych.2006.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Configural Cue Performance in Identical Twins Discordant for Posttraumatic Stress Disorder: Theoretical Implications for the Role of Hippocampal Function

Abstract: Background-A significant subgroup of individuals with posttraumatic stress disorder (PTSD) exhibits chronic, unremitting symptomatology that has also been associated with smaller hippocampal volume. The hippocampus plays a significant role in configural processing of contextual cues that facilitates context-appropriate extinction of conditioned fear. We test the hypothesis that hippocampus-based configural processing deficits are a pre-existing vulnerability factor for unremitting forms of PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
83
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(98 citation statements)
references
References 78 publications
12
83
3
Order By: Relevance
“…Hippocampal reduction may also be a preexisting vulnerability factor rather than a general consequence of PTSD. 54 As previously noted, 12 the convergent structural neuroimaging findings in patients with PTSD and those with depression raise issues about whether models of the neurocircuitry of PTSD 55 reflect common vulnerabilities to different types of psychopathology. Similar models have also been put forward to account for mood alterations in patients with depression.…”
Section: Discussionmentioning
confidence: 97%
“…Hippocampal reduction may also be a preexisting vulnerability factor rather than a general consequence of PTSD. 54 As previously noted, 12 the convergent structural neuroimaging findings in patients with PTSD and those with depression raise issues about whether models of the neurocircuitry of PTSD 55 reflect common vulnerabilities to different types of psychopathology. Similar models have also been put forward to account for mood alterations in patients with depression.…”
Section: Discussionmentioning
confidence: 97%
“…Hippocampal volume and declarative memory function in combat-related PTSD Hippocampal volume and declarative memory in PTSD 831 et al, 2008 ;Lang et al, 2009 ) and perhaps subservient to these, confi gural cue processing (Gilbertson et al, 2007 ). There is a danger that such alternative avenues for understanding the hippocampus in PTSD could be under-researched to the extent that a declarative memory framework is overvalued.…”
Section: Symposiummentioning
confidence: 99%
“…To date, the most direct evidence in support of the dualrepresentation model comes from two studies that assessed individual differences in visuospatial processing abilities and related them to PTSD symptoms (Bisby, King, Brewin, Burgess, & Curran, 2010;Gilbertson et al, 2007). In an elegant twin study, Gilbertson et al showed that PTSD was marked by impaired allocentric visuospatial processing, as measured with a 20-item multiple-choice task in which participants had to rotate cubes in their minds or visualize how papers would be folded.…”
mentioning
confidence: 99%